Evaluation of Antioxidant, Anticholinesterase and Antityrosinase Activities of Malaysian Cinnamomum Species - Salleh, Wan Mohd Nuzul Hakimi Wan; Ahmad, Farediah; Yen, Khong Heng (Dhaka University Journal of Pharmaceutical Sciences, 2016)
The extracts of the leaves and bark of five Cinnamomum species (C. altissimum, C. griffithii, C. javanicum, C. macrocarpum, and C. velutinum) were screened to evaluate their antioxidant, anticholinesterase, and antityrosinase activities. The bark of C. altissimum showed the highest phenolic content (130.1 mg GA/g), free radical scavenging by DPPH (IC50 126.2 ?g/mL) and ferric reducing antioxidant power (FRAP) assays (341.2 mg AA/g). All of the extracts inhibited linoleic acid peroxidation by greater than 70%, with the leaves of C. altissimum exhibiting the highest inhibition of 87.7%. The leaves of C. javanicum revealed the highest inhibition on anticholinesterase (AChE 30.8%) and butyrylcholinesterase (BChE 46.8%) enzymes. The leaves and bark of C. altissimum and C. velutinum exhibited greater than 20% tyrosinase inhibition, with the leaves of C. altissimum having the highest percentage of inhibition (34.6%). These bioactivities indicate that some Cinnamomum species have therapeutic potential in medicinal research and development of new drugs candidates. Dhaka Univ. J. Pharm. Sci. 14(2): 125-132, 2015 (December)